Translation and Validation of the Brazilian Portuguese Version of the Broad Conceptualization of Beauty Scale With Brazilian Women. (September 2021) - Junqueira, Alessandra Costa Pereira; Tylka, Tracy L.; Almeida, Sebastião de Sousa; Costa, Telma Maria Braga; Laus, Maria Fernanda
In many countries, women are socialized to adopt a narrow definition of beauty. Research has revealed that, in the United States and China, the ability to broadly conceptualize beauty (perceive beauty in diverse body sizes, shapes, and appearances) is linked to women's lower anti-fat attitudes, higher body appreciation, and higher well-being. In this study, we translated an existing measure of this construct, the Broad Conceptualization of Beauty Scale (BCBS), into Brazilian Portuguese and evaluated the factor structure and reliability and validity of its scores with a diverse sample of 563 Portuguese women. Findings revealed that the Brazilian Portuguese BCBS contains two factors—external/appearance features of beauty (BCBS-E) and internal features of beauty (BCBS-I)—contrary to the unidimensional factor structure found in previous studies. Support for internal consistency and 3-week test–retest reliability was garnered. Total BCBS and BCBS-E scores evidenced convergent, discriminant, and incremental validity, whereas the BCBS-I did not accrue substantial convergent or incremental validity support beyond its inverse bivariate association with anti-fat attitudes. We recommend the use of the Brazilian Portuguese BCBS in body image research programs as well as clinical practice and prevention programs with Brazilian women seeking support for body dissatisfaction and disordered eating.